"Click Chemistry" for the Simple Determination of Fatty‐Acid Uptake and Degradation: Revising the Role of Fatty‐Acid Transporters. Issue 11 (11th June 2015) - Pérez, Alexander J.; Bode, Helge B.
Abstract Fatty acids (FAs) have numerous functions in all living organisms, ranging from structural roles and energy production to the biosynthesis of secondary metabolites. Because of the high energy content of exogenous FAs, their acquisition is central of metabolism, and several biological systems are known, although their precise roles are not yet entirely clear. We investigated the roles of FadD (CoA ligase) and FadL (FA transporter) in different bacterial strains by using an improved version of click‐chemistry‐assisted labelling of azido‐FAs. The high sensitivity of this method allows a direct and precise assessment of FA metabolism, and is thus far better suited than growth experiments. Our results show that although FA activation is indeed essential for FA degradation, their transport can be independent of transporters like FadL.